Рeculiarities of interaction of low-energy protons with tungsten surface - Fedorovich, O.A.; Hladkovskyi, V.V.; Polozov, B.P.; Voitenko, L.M.; Kostin, E.G.; Petriakov, V.А.; Rokitskyi, А.A.; Oberemok, А.S.; Burdin, V.V. (Вопросы атомной науки и техники, 2018)
The results of investigations of the interaction of protons with energy of 250…260 eV with the surface of tungsten foil are presented. Sputtering of tungsten occurs at a rate of ~ 0.5 μm/h at a temperature of 300°C and an ion
current density of 1.5 mA/cm²
. The surface of tungsten significantly changes after the irradiation process. The substantial surface cleaning occurs from oxides due to surface sputtering, and also because of their reduction in hydrogen plasma. The hydrogen content increases near the surface of the tungsten sample after irradiation with protons.
The hydrogen content decreases in depth in tungsten. Наведено результати досліджень взаємодії протонів з енергією 250…260 еВ з поверхнею вольфрамової
фольги. Відбувається розпорошення вольфраму зі швидкістю ~ 0,5 мкм/год при температурі 300°С і щільності іонного струму ~ 1,5 мА/см²
. Поверхня вольфраму значно змінюється після процесу опромінення. Відбувається істотне очищення поверхні від оксидів через розпорошення поверхні, а також із-за їх відновлення у
водневій плазмі. Після опромінення вольфраму протонами істотно збільшується вміст водню поблизу поверхні зразка. Вміст водню у вольфрамі повільно зменшується по глибині. Приведены результаты исследований взаимодействия протонов с энергией 250…260 эВ с поверхностью
вольфрамовой фольги. Происходит распыление вольфрама со скоростью ~ 0,5 мкм/ч при температуре 300°С
и плотности ионного тока ~ 1,5 мА/см²
. Поверхность вольфрама значительно изменяется после процесса
облучения. Происходит существенная очистка поверхности от оксидов из-за распыления поверхности, а
также из-за их восстановления в водородной плазме. После облучения вольфрама протонами существенно
увеличивается содержание водорода вблизи поверхности образца. Содержание водорода в вольфраме плавно уменьшается по глубине.